5 Catalase Inhibition Augments Reactive Oxygen Species Production in Isolated Ventricular Myocytes. (19th January 2014) - Boles, S; Polak, A; Littlejohns, B; Lin, H; Suleiman, M S
Abstract : Myocardial damage during ischaemia-reperfusion is partly mediated by the accelerated production of reactive oxygen species (ROS). Under physiological conditions, antioxidants, such as catalase, regulate ROS levels. The capacity for elevated catalase levels to offer cardio-protective benefits to hearts exposed to ischaemia-reperfusion has been demonstrated previously. However, no studies thus far have selectively inhibited catalase in isolated cardiomyocytes, This study investigated the importance of endogenous catalase in regulating ROS generation basally and during oxidative stress by using the catalase inhibitor, 3-amino-1, 2, 4-triazole (3-AT). Cardiomyocytes were isolated from adult rat hearts. Cells were loaded with 5-(and-6)-chloromethyl-2', 7'-dichlorodihydrofluorescein diacetate acetyl ester (CM-H2DCFDA) in the presence or absence of different concentrations of 3-AT (0–40 mM). The ROS production rate in quiescent cardiomyocytes was estimated by measuring the fluorescence signal emitted by 5-(and 6)-chloromethyl-2′, 7′-dichlorofluorescein, using a fluorescence plate reader. Incubation with 3-AT did not affect the ROS generation rate under basal conditions. However, upon addition of 10 mM H2 O2, 3-AT administration resulted in a dose-dependent increase in the ROS generation rate (P < 0.0001). This increase plateaued with 20 mM 3-AT, which resulted in a near-tripling of the mean ROS generation rate compared to 0 mM 3-AT (P < 0.01). This study demonstrates that endogenous catalase has a limited contribution to the regulation of ROS levels in resting, unstressed cardiomyocytes. However, its activity appears important in reducing the ROS generation rate when intracellular H2 O2 levels are elevated. We conclude that, despite the low levels of endogenous catalase present in cardiomyocytes, its regulation of ROS generation is very important during conditions of significant oxidative stress.